PENERAPAN SUPERVISI AKADEMIK UNTUK MENINGKATKAN KOMPETENSI GURU DALAM MENYUSUN ADMINISTRASI PENILAIAN DI SDN 020 LENGKONG BESAR - Supono (GoAcademica Research dan Publishing, 2022)
The purpose of this school action research is to increase the Competence of Teachers of State Elementary School 020 Lengkong Besar in Compiling Assessment Administration through academic supervision. The research method used was a classroom/school action research method with 2 cycles, each consisting of four stages, namely planning, implementing, observing and reflecting. The results of data analysis showed that there was an increase in teacher competence from cycle to cycle. This is shown by the analysis of teacher competence in each cycle. In cycle I, that is, out of 12 supervised teachers, it was found that 5 people or 41.67% had the competence to compose a good assessment administration. In cycle II, there has been an increase, namely from 12 supervised teachers, it was found that 10 people or 83.33% had good teacher competence. Thus, this already meets the performance indicators in this study, namely if the competence of teachers in compiling administration of assessments at State Elementary School 020 Lengkong Besar reaches a percentage of 75%, then the research is considered successful. The conclusion from this study is that academic supervision can improve teacher competence in preparing assessment administration at State Elementary School 020 Lengkong Besar. This is indicated by an increase from the initial observation, cycle I and cycle II.